Microgreens: Acceptance and Perception of Consumers - Rawat, Kritika; Pahuja, Aastha; Sharma, Russell; Jain, Monika (Annals of Arid Zone, 2024)
Microgreens, young greens derived from various plant seeds are packed with essential nutrients and bioactive compounds. Farmers invest in them due to high market demand and rapid production cycle. With their abundance of phytochemicals, microgreens demonstrate strong antioxidant properties and have the potential to prevent chronic diseases. All around the globe there is a proactive search for health-promoting foods and microgreens can be the answer. The current study assessed the consumer perception and acceptance of microgreens. An online survey was administered and was answered by 150 people aged 20-35 years to assess consumer awareness about microgreens. A ranking scale and 5-point Likert scale were employed to rank the constraints in purchasing microgreens and to assess consumers’ perception, respectively. In addition, a sensory analysis of five microgreen varieties i.e., radish (white, purple, and pink), beetroot, and carrot was carried out in the campus of Banasthali Vidyapith by an untrained panel of 100 people using a 9-point hedonic scale. The results of online survey revealed that only 100 respondents out of 150 were familiar with microgreens hence answered further question which were regarding their understanding of microgreens. A positive inclination towards microgreens was seen, especially regarding their benefits on personal and gut health. Few constraints such as lack of awareness, high perishability, and pricing concerns were also highlighted by the general population. Additionally, the results of sensory evaluation revealed that the 64.6% consumers expressed a liking for microgreens. Beetroot and carrot microgreens varieties were most accepted by consumers.